2021
DOI: 10.1039/d1ra03043d
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted acid-promoted hydroamination of unsaturated hydrazones: access to biologically important 5-arylpyrazolines

Abstract: An efficient, chemo- and regioselective Brønsted acid-promoted hydroamination reaction of hydrazone-tethered olefins towards 5-arylpyrazolines was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 132 publications
0
3
0
Order By: Relevance
“…The addition of the radical scavenger BHT had no effect on the outcome of the reaction, indicating that the reaction proceeds via an ionic and not a radical pathway. Interestingly, while the protocol gives access to pyrazolines with various substituents, the use of a hydrazone with R 4 =H did not yield the monosubstituted product [87a] . Previously, it was found that another acid, trifluoromethanesulfonic acid (TfOH), is able to promote three component reactions between aldehydes 279 , arylhydrazines 280 and styrene 281 towards aryl trisubstituted pyrazolines 282 (Scheme 57b).…”
Section: Intramolecular Cyclizations Of Unsaturated Hydrazonesmentioning
confidence: 99%
“…The addition of the radical scavenger BHT had no effect on the outcome of the reaction, indicating that the reaction proceeds via an ionic and not a radical pathway. Interestingly, while the protocol gives access to pyrazolines with various substituents, the use of a hydrazone with R 4 =H did not yield the monosubstituted product [87a] . Previously, it was found that another acid, trifluoromethanesulfonic acid (TfOH), is able to promote three component reactions between aldehydes 279 , arylhydrazines 280 and styrene 281 towards aryl trisubstituted pyrazolines 282 (Scheme 57b).…”
Section: Intramolecular Cyclizations Of Unsaturated Hydrazonesmentioning
confidence: 99%
“…21 Inspired by Jiang's 8 b and our previous work, 21 we wondered whether it would be possible to use oximes, aldehydes, and amines to synthesize structurally diverse N-heterocycles. Based on our continuous interest in photoredox catalysis and heterocyclic synthesis, 22 we report herein the dual photoredox/copper catalyzed multicomponent reactions of oxime esters, aldehydes, and amines, which provide a straightforward and efficient approach toward fully substituted 1 H -imidazoles in good yields (Scheme 1c, right). To the best of our knowledge, the construction of fully substituted 1 H -imidazoles with oxime esters under dual photoredox/copper catalysis has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, intramolecular aminocyclization of β,γ-unsaturated hydrazones have been well exploited via transition-metal-catalyzed, photocatalytic, and metal-free reaction pathways for the efficient access of functionalized pyrazolines (Scheme a). This intramolecular cyclization strategy has also been adopted for aminocyclization of N-propargyl sulfonylhydrazine in the presence of an expensive palladium catalyst, which afforded a mixture of pyrazole and pyrazoline, indicating the free amino group present in the the starting material is more reactive and less selective (Scheme b) . Interestingly, in a similar reaction protocol, N -propargyl tosylhydrazone, where the amino group is protected, readily cyclized to afford N -tosyl pyrazoline in the presence of expensive ruthenium and silver catalysts, although the reaction yield, scope, selectivity, functional group tolerance, and detailed mechanism of the reaction were unexplored (Scheme c) .…”
mentioning
confidence: 99%